2019
DOI: 10.3390/polym11081320
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Toughening of 2,6-Diaminopyridine Derived Poly (Urethane Urea) via Dynamic Cross-Linkages and Interfering with Hydrogen Bonding of Urea Groups from Partially Coordinated Ligands

Abstract: Conventional approaches to synthesize thermoplastic polyurethane (TPU) with excellent robustness are limited by a competing relationship between soft and hard segments for tuning mechanical properties in terms of chain flexibility and micro-phase separation. Herein, we present a facile and effective way of simultaneously improving the tensile strength, elongation, and toughness by constructing dynamic cross-linkages from metal-ligand interaction between Zn2+ and pyridine moiety in backbone of poly(urethane ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…In addition, compared with PU-L (without the addition of zinc ions), the absorption peaks of amide I, amide II, and amide III bands in the PU-L/Zn curve show significant changes, indicating that the O and N atoms in the urea bond participate in coordination with Zn­(II) and also that the formation of coordination bonds has an effect on the formation of hydrogen bonds between urea groups, which is consistent with the results of the related literature. , As shown in the UV–vis spectrum of Figure g, the PU-L solution shows two absorption peaks centered at ∼244 and 306 nm, assigning to the n → π* transition of urea groups and the π → π* transition of pyridine groups, respectively . By contrast, the addition of Zn­(II) resulted in a new feature peak in the UV spectrum of PU-L/Zn-3 at ∼276 nm, which is attributed to the characteristic absorbance of the Zn-urea charge-transfer electronic transition. , In addition, a bathochromic shift of the pyridine ligand-centered π–π* electronic transition is observed in Figure g . All the above results can prove the formation of coordination bonds, and the nitrogen heterocycle as well as N and O atoms in the urea bond are able to coordinate with Zn­(II), thus forming strong physical cross-links in the polyurea network.…”
Section: Resultssupporting
confidence: 89%
“…In addition, compared with PU-L (without the addition of zinc ions), the absorption peaks of amide I, amide II, and amide III bands in the PU-L/Zn curve show significant changes, indicating that the O and N atoms in the urea bond participate in coordination with Zn­(II) and also that the formation of coordination bonds has an effect on the formation of hydrogen bonds between urea groups, which is consistent with the results of the related literature. , As shown in the UV–vis spectrum of Figure g, the PU-L solution shows two absorption peaks centered at ∼244 and 306 nm, assigning to the n → π* transition of urea groups and the π → π* transition of pyridine groups, respectively . By contrast, the addition of Zn­(II) resulted in a new feature peak in the UV spectrum of PU-L/Zn-3 at ∼276 nm, which is attributed to the characteristic absorbance of the Zn-urea charge-transfer electronic transition. , In addition, a bathochromic shift of the pyridine ligand-centered π–π* electronic transition is observed in Figure g . All the above results can prove the formation of coordination bonds, and the nitrogen heterocycle as well as N and O atoms in the urea bond are able to coordinate with Zn­(II), thus forming strong physical cross-links in the polyurea network.…”
Section: Resultssupporting
confidence: 89%
“…The ATR-FTIR spectra of PDMS-DAP@Fe- x shown in Figure b reflect that the amide I band at 1636 cm –1 and amide II band at 1572 cm –1 shifted to 1626 and 1576 cm –1 , respectively, suggesting the coordination between Fe­(III) and urea group. Besides, the disappearance of peak at 1684 cm –1 validates the coordination between Fe­(III) and O in the urea group. , The UV–vis spectra of the prepared elastomers were characterized to further verify the existence of coordination bonding interactions. As shown in Figure c, upon introduction of Fe­(III) ions, a new absorption at 336 nm appeared, verifying the coordination between Fe­(III) and N pyridine . , However, the decreasing solubility of hybrid networks caused by the increased coordination networks led to the decrease of the band strength.…”
Section: Resultsmentioning
confidence: 89%
“…Besides, the disappearance of peak at 1684 cm −1 validates the coordination between Fe(III) and O in the urea group. 36,37 The UV−vis spectra of the prepared elastomers were characterized to further verify the existence of coordination bonding interactions. As shown in Figure 1c, upon introduction of Fe(III) ions, a new absorption at 336 nm appeared, verifying the coordination between Fe(III) and N pyridine .…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that all materials exhibit a single T g , which indicates that the materials are not phase separated, which could be beneficial to chain mobility. [20] ISPU and IMPU were uniaxially strained at a strain rate of 10 mm min À 1 to initially assess their mechanical properties. This revealed that the ISPU behaved comparably to IMPU, [18] both as tough elastomers with high tensile strength and extensibility at failure.…”
Section: Resultsmentioning
confidence: 99%